Safety and accessibility of pedestrian infrastructural network at MRT stations in Singapore - Yap, Tzyy Kae. (2011)
The main purpose of this research project is to investigate the safety and accessibility of pedestrian infrastructural network at MRT stations in Singapore. The six stations selected are namely: Ang Mo Kio, Bedok, Boon Lay, Chinese Garden, Queenstown and Redhill. The first 3 stations are classified as integrated stations where they are integrated with bus interchange and shopping malls/town centre. The latter three are classified as non-integrated stations, meaning they are standalone station, with no such facilities.